Characterization of the major locus of immediate-early genes of rat cytomegalovirus. - Sandford, G R (J Virol, 1993)
A major locus of rat cytomegalovirus (RCMV) immediate-early (IE) RNA transcription was identified. A cDNA library from rat embryo fibroblasts infected with RCMV under IE conditions was constructed and screened by using appropriate RCMV DNA probes, revealing at least two IE genes (IE1 and IE2) transcribed from this locus by differential splicing. The first three exons (the first is noncoding) are spliced to exon 4 to form IE1 and to exon 5 to form IE2. The structural organization of the RCMV major IE region is therefore similar to that of human cytomegalovirus (HCMV) and murine cytomegalovirus (MCMV). When we compared the predicted amino acid sequences of the IE1 proteins of RCMV, HCMV, and MCMV, no areas of homology were found across all three proteins, while a few small areas of homology were found between RCMV IE1 and MCMV IE1. In contrast, large areas of homology were found across the carboxyl half of RCMV IE2, HCMV IE2, and MCMV ie3 proteins. In addition, similarities were found at the beginning of exon 5 of RCMV and MCMV. The possible significance of these conserved regions is discussed. Dinucleotide frequency analysis demonstrated a decrease in CpG frequency over the IE region. The IE gene products were able to transactivate heterologous promoters. IMAGES: